Gender prejudice against homosexual university students at a public university in Mexico City (Praxis Educativa, 2021)
In Mexico, sexual orientation continues to be a factor of discrimination. People's perception of homosexuality still tends to be prejudiced. The objective of this article is to describe the gender biases of heterosexual students towards homosexual students at a public institution of higher education in Mexico City. The methodology used is quantitative. The study was descriptive and cross-sectional, with a non-probability sample of 100 heterosexual university students; 24 were male and 76 female, with an average age of 24 years. Prejudices were measured through three likert scales: cognitive (stereotype scale), affective (emotion scale) and behavioral (social distance scale). The findings open up the possibility of modifying gender prejudices by sexual orientation to consider positive attitudes and good treatment of people, recognizing that they have the same rights and obligations before the law of the country.
Keywords: prejudices; sexual diversity; gender stereotypes; discrimination